Optimization of cultural conditions for omega 3-6 fatty acids and carotenoids production by \( Schizochytrium mangrovei\) TB17 - Thom, Le Thi; Ha, Nguyen Cam; Hong, Dang Diem (Academia Journal of Biology, 2022)
Heterotrophic marine microalgae Thraustochytrids are commonly found in marine environments, sediments, and decaying mangrove leaves. Their ability to produce high-value products such as docosahexaenoic fatty acids (DHA, C22:6 ω-3), carotenoids, and sterols has gained increasing attention. The products are widely applied in the food, pharmaceutical, and cosmetic industries. In this paper, results on the effect of culture medium on fatty acid composition and pigment content as carotenoid and astaxanthin of Schizochytrium mangrovei TB17 strain biomass were presented. The optimal growth conditions of strain TB17 in the flask were determined including the temperature of 28 oC, the salt concentration of 15‰, glucose as carbon source with the concentration of 3%, yeast extract as nitrogen source with the concentration of 1%. Dry cell weight (DCW) and lipid content of strain TB17 reached highest values of 12.61 ± 0.16 g/L; 34.17 ± 1.92% DCW, respectively, after 120 hours of culture. The content of DHA, docosapentaenoic acid (DPA, C22:5 ω-3) and eicosapentaenoic acid (EPA, C20:5 ω-3) in biomass accounted for 36.66 ± 1.63%; 11.73 ± 1.14% and 0.48 ± 0.01% of total fatty acid (TFA), respectively. The content of total carotenoid and astaxanthin reached 35.86 ± 1.52 µg/g and 7.18 ± 0.21 µg/g DCW after 120 hours of culture. Therefore, the obtained biomass of strain TB17 was sufficient to meet the demand for the production of DHA, DPA, EPA fatty acids as well as the extraction of carotenoids, especially astaxanthin for functional food and other biotechnological applications.